2021
DOI: 10.3390/w13202840
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Flow Regime along the River Vistula

Abstract: The flow regime in the River Vistula is influenced by climatic and geographical factors and human intervention. In this study, we focus on an analysis of flow and precipitation variability over time and space following the course of the River Vistula. Multi-purpose statistical analyses of a number of runoff and precipitation characteristics were performed to present a general overview of the temporal and spatial changes. Since the important feature of the hydrological regime of Polish rivers is the seasonality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Testing the homogeneity and stationarity of a maximum precipitation series is often overlooked in studies on the design of DDF or IDF curves, and it is assumed that this condition is met [5,6,42,65]. The results of the homogeneity of the series of seasonal maximum precipitation of Polish stations investigated here are consistent with the literature, since, unlike in other European countries, no statistically significant trends in both seasonal and annual precipitation totals were found in Poland and Slovenia [66][67][68]. Only Mły ński et al [27] found a growing significant trend in the annual maximum daily precipitation for the period 1971-2014 (i.e., a period shorter than the one treated of here) at the level of 0.05 for 12% of 51 meteorological stations surveyed in the Upper Vistula region.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Testing the homogeneity and stationarity of a maximum precipitation series is often overlooked in studies on the design of DDF or IDF curves, and it is assumed that this condition is met [5,6,42,65]. The results of the homogeneity of the series of seasonal maximum precipitation of Polish stations investigated here are consistent with the literature, since, unlike in other European countries, no statistically significant trends in both seasonal and annual precipitation totals were found in Poland and Slovenia [66][67][68]. Only Mły ński et al [27] found a growing significant trend in the annual maximum daily precipitation for the period 1971-2014 (i.e., a period shorter than the one treated of here) at the level of 0.05 for 12% of 51 meteorological stations surveyed in the Upper Vistula region.…”
Section: Discussionsupporting
confidence: 87%
“…Only Mły ński et al [27] found a growing significant trend in the annual maximum daily precipitation for the period 1971-2014 (i.e., a period shorter than the one treated of here) at the level of 0.05 for 12% of 51 meteorological stations surveyed in the Upper Vistula region. Referring to the maximum flows, the trends in daily flow maxima on the Vistula and some of its tributaries in the seasonal timeframe were studied in [68]. The research did not reveal any significant changes in the high waters regime.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal changes in flows are directly related to climate change in the area [32] and have a direct impact on flood hazard mapping [33]. According to hydrological and climatological research conducted in the Carpathian area, even greater variability in droughts and floods can be expected in the future [34][35][36][37]. As a result, there is a need for tools that can automatically track these changes.…”
Section: Resultsmentioning
confidence: 99%
“…The available photographic documentation from the studied stream cross-section did not contain a sufficient number of images from the flood; therefore, three additional photos were analyzed (Figure 10). even greater variability in droughts and floods can be expected in the future [34][35][36][37]. As a result, there is a need for tools that can automatically track these changes.…”
Section: Resultsmentioning
confidence: 99%
“…In order to explain Vistula's water resource modifications, its tributaries' water capital must be examined, together with the land use transformation and the water volume withdrawn for different economic activities. Regarding inland navigation, Vistula's water capital decreasing tendency is not acceptable and important measures in this direction should be taken; (e) There is no important trend in the seasonal and annual precipitation totals and flow volumes on Vistula's course, but the increasing temperatures, followed by the field evaporation growth, will enhance the summer-autumn dryness danger if the total rainfall does not change [48].…”
Section: Image Classificationmentioning
confidence: 99%